Relevance of hepatic preneoplasia for human hepatocarcinogenesis: $hQin Su and Peter Bannasch - Su, Qin; Bannasch, Peter (Toxicologic pathology, 2003)
Different lesions have been suggested to represent preneoplastic conditions in human liver. They include liver cell dysplasia, separated in large-cell change (LCC) and small-cell change (SCC), adenomatoid hyperplasia, and the more recently identified foci of altered hepatocytes (FAH) and nodules of altered hepatocytes (NAH). FAH have been demonstrated to represent preneoplastic lesions in various animal models of hepatocarcinogenesis.